Phenotypic stability of traits associated with fruit quality in butternut squash (cucurbita moschata duch.) (2013)
The aim of this study was to identify and select genotypes with high fruit dry matter, represented by high starches and carotenes, to obtain a cultivar apt for agroindustrial processes. The model of Eberhart and Russell was used to measure the stability parameter and evaluate the phenotypic stability of traits associated with fruit quality in four populations of butternut squash at three localities in the department of Valle del Cauca (Colombia): Candelaria, Palmira and El Cerrito. Highly significant differences were detected for the genotype x location (P≤0.001) interaction for the traits of dry matter, carotene and starch. Except for population 1 in El Cerrito, there was a negative effect on the accumulation of photosynthates at 1,536 m a.s.l., probably due to the low quality of the heliophany. The populations 1, 2 and 3 were stable and predictable, complying with the parameters β = 1 and d = 0 of the Eberhart and Russell methodology. Population 1 was notable in terms of high fruit production, high dry matter content and good phenotypic stability.